Sequential and simultaneous choices: testing the diet selection and sequential choice models - Freidin, E; Aw, J; Kacelnik, A (Elsevier, 2009)
We investigate simultaneous and sequential choices in starlings, using Charnov's Diet Choice Model(DCM) and Shapiro, Siller and Kacelnik's Sequential Choice Model (SCM) to integrate function and mechanism. During a training phase, starlings encountered one food-related option per trial (A, B or R) in random sequence and with equal probability. A and B delivered food rewards after programmed delays (shorter for A), while R ('rejection') moved directly to the next trial without reward. In this phase we measured latencies to respond. In a later, choice, phase, birds encountered the pairs A–B, A–R and B–R, the first implementing a simultaneous choice and the second and third sequential choices. The DCM predicts when R should be chosen to maximize intake rate, and SCM uses latencies of the training phase to predict choices between any pair of options in the choice phase. The predictions of both models coincided, and both successfully predicted the birds’ preferences. The DCM does not deal with partial preferences, while the SCM does, and experimental results were strongly correlated to this model’s predictions. We believe that the SCMmay expose a very general mechanism of animal choice, and that its wider domain of success reflects the greater ecological significance of sequential over simultaneous choices.